Melacak prinsip pemikiran Pendidikan Islam melalui Filsafat Klasik; Socrates, Plato dan Aristoteles. - Trya Imamatul Istiqomah; Aulia Salsabila; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
How the emergence of ancient philosophy can influence Islamic education. This article explores the emergence of ancient philosophy and its influence in the perspective of the philosophy of Islamic education. Starting from the thoughts of Greek philosophers such as Socrates, Plato, and Aristotle, the concept of education they developed became an important foundation for the development of education in the Islamic world. Socrates with his dialogical method, Plato with the concept of education in the “Republic